Fabrication of Silver Nanoparticles Against Fungal Pathogens - Mansoor, Sheikh; Zahoor, Irfana; Baba, Tawseef Rehman; Padder, Shahid A.; Bhat, Z. A.; Koul, Aabid Mustafa; Jiang, Linghuo (Frontiers in Nanotechnology, 2021)
The use of silver nanoparticles (AgNPs) against various pathogens is now being well recognized in the agriculture and health sector. Nanoparticles have been shown to exhibit various novel properties and these properties on other hand rely upon the size, shape and morphology of these particles. Moreover, these physical characteristics enable them to interact with microbes, plants and animals. Smaller sized particles have shown more toxicity than larger sized nanoparticles. AgNPs have shown growth inhibition of many fungi like Aspergillus fumigates, A. niger, A. flavus, Trichophyton rubrum, Candida albicans and Penicillium species. According to the current hypothesis, AgNPs act by producing reactive oxygen species and free radicals, which causes protein denaturation, nucleic acid and proton pump damage, lipid peroxidation and cell wall damage. Therefore, they alter the cell membrane permeability, causing cell death. This mini-review summarizes the use of silver nanoparticles against fungal pathogens and fungal biofilm in the agricultural sector.